Constitutional Internalization of Islamic Law in a Pancasila State - Adi Prihasmoro; Chaerul Anwar; Yayan Sopyan; Raihanah Abdullah; Riris Ardhanariswari (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2026)
This article aims to provide a positive perspective on the contribution of Islamic law since the birth of the Unitary State of Indonesia (NKRI), UUD 1945, and Pancasila. The research was conducted through a literature study tracing the history of implementing Islamic law and its internalization into the national legal system, alongside the development of an increasingly religious Indonesian population. In the post-Reformation era, Islamic law appears to have gained momentum in shaping national law. The romanticism of the nation's religious ambition to believe in God, with the obligation to carry out sharia for its adherents, comes back alive and rises. That nation's religious ambition is recorded in the history of the Pancasila version of the Jakarta Charter in 1945. This spirit has been integrated into the history of the birth of the Republic of Indonesia, the UUD 1945, and Pancasila, and remains alive and deeply rooted in the nation spirit. The study shows that in the NKRI, Islamic law could be applied lawfully. It is implemented constitutionally based on Pancasila. The integration of Islamic law that characterizes national law can work without reducing the rights and obligations of adherents of other religions in Indonesia.